FAKTOR-FAKTOR YANG MEMPENGARUHI PARTISIPASI IBU RUMAH TANGGA DALAM MENJAGA SANITASI DI PERUMAHAN PT.PERKEBUNAN NUSANTARA VI (PERSERO) KECAMATAN LUHAK NAN DUO KABUPATEN PASAMAN BARAT - Pasaribu, Rehuela Ziporatua (Pendidikan Geografi, 2014)
This study aims to determine: Factors Affecting Participation in KeepingHousewife Sanitation Housing PT. Plantation Nusantara VI (Persero) District Luhak NanDuo Regency West PasamanThe research is a descriptive correlation. The population in this study amounted to416 Housewife and samples were taken with a sampling technique rondom magnitudeproportional porposi samples was determined that 20% of the study sample size was 83housewife.The results of this study indicate that: 1) Knowledge significant effect onparticipation housewife in keeping sanitation in Housing PT. Plantation Nusantara VI(Persero) District Luhak Nan Duo Regency West Pasaman, a contribution of (25.90%). 2)Concern significant effect on the participation of housewives in maintaining sanitation inHousing PT. Plantation Nusantara VI (Persero) District Luhak Nan Duo Regency WestPasaman, a contribution of (37.80%). 3) leisure time significantly influence the participationof housewives in maintaining sanitary in Housing PT. Plantation Nusantara VI (Persero)District Luhak Nan Duo Regency West Pasaman, a contribution of (16.20%.). 4) Knowledge,awareness, and free time together significant effect on participation housewife in keepingsanitation in Housing PT. Plantation Nusantara VI (Persero) District Luhak Nan DuoRegency West Pasaman, a contribution of (72.60%.).